An Analysis of Incidence, Related Factors and Prophylactic Treatments of Hospital-Acquired Upper Extremity Deep Vein Thrombosis: A Single-Center 13-Year Retrospective Study - Xiao Wang MD; Yezu Liu MD; Jing Wang MD; Chun Bai MD; Xiaoming Zhang MD; Xuemin Zhang MD; Qingle Li MD; Wei Li MD; Jingjun Jiang MD; Yang Jiao MD; Tao Zhang MD (Clinical and Applied Thrombosis/Hemostasis)
Objectives This study aimed to evaluate the incidence trend and related factors for hospital-acquired upper extremity deep vein thrombosis (HA-UEDVT) in inpatients of a large medical center in China over 13 years, and to summarize and analyze the complications and preventive treatments of HA-UEDVT. Methods We conducted a retrospective analysis on the epidemiological characteristics, related factors, and use of different prophylactic anticoagulation methods in patients with HA-UEDVT at Peking University People's Hospital from January 1, 2009, to December 31, 2021. The data of all patients were obtained through the hospital's medical record system. Results Over the 13 years, there has been 239 cases of HA-UEDVT, with a much lower incidence rate compared to HA-LEDVT (0.31 vs 2.28 per 1000 admissions). HA-UEDVT incidence peaked in 2015 and 2016 (both 0.44 per 1000 admissions). The highest HA-UEDVT incidence rates were in the respiratory and gastroenterology departments, with 1.13 and 1.22 per 1000 admissions, respectively. The top three related factors of HA-UEDVT were having a CVC, concurrent of breast cancer, and concurrent of HA-LEDVT, with the β values of 4.81, 4.68, and 3.11, respectively. Thrombosis-related preventive measures were implemented in 30.1% of patients, significantly less frequently than HA-LEDVT (30.1% vs 82.4%, p  < .001). The low molecular weight heparin (LMWH) subcutaneous injection being the main thromboprophylaxis used before HA-UEDVT diagnosis. Conclusions HA-UEDVT mainly occurred in medicine departments and has shown a decreasing trend in recent years. Having CVC, breast cancer, and HA-LEDVT are highly associated with HA-UEDVT occurrence. There was no statistical difference in the incidence of pulmonary embolism between CVC-related HA-UEDVT and HA-LEDVT groups. More high-quality prospective studies are needed to guide HA-UEDVT prevention.